2006
DOI: 10.1038/nature04596
|View full text |Cite
|
Sign up to set email alerts
|

Toll-dependent selection of microbial antigens for presentation by dendritic cells

Abstract: Dendritic cells constitutively sample the tissue microenvironment and phagocytose both microbial and host apoptotic cells. This leads to the induction of immunity against invading pathogens or tolerance to peripheral self antigens, respectively. The outcome of antigen presentation by dendritic cells depends on their activation status, such that Toll-like receptor (TLR)-induced dendritic cell activation makes them immunogenic, whereas steady-state presentation of self antigens leads to tolerance. TLR-inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
614
4
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 732 publications
(646 citation statements)
references
References 30 publications
21
614
4
7
Order By: Relevance
“…This phenotype was the consequence of a defect in the delivery of lysosomal proteases to phagosomes, as well as a delay of fusion of phagosomes with lysosomes. The precise mechanism of how the macroautophagy machinery is recruited to phagosomes and might enhance fusion with lysosomes remains unclear, but these findings are in line with previous studies, documenting enhanced antigen presentation of TLR ligand coated antigen and Atg supported fusion of phagosomes containing such antigen with lysosomes [39][40] . In one of these studies, the authors described that TLR engagement induces "LC3-associated phagocytosis" (LAP).…”
Section: Endogenous Pathwaysupporting
confidence: 85%
“…This phenotype was the consequence of a defect in the delivery of lysosomal proteases to phagosomes, as well as a delay of fusion of phagosomes with lysosomes. The precise mechanism of how the macroautophagy machinery is recruited to phagosomes and might enhance fusion with lysosomes remains unclear, but these findings are in line with previous studies, documenting enhanced antigen presentation of TLR ligand coated antigen and Atg supported fusion of phagosomes containing such antigen with lysosomes [39][40] . In one of these studies, the authors described that TLR engagement induces "LC3-associated phagocytosis" (LAP).…”
Section: Endogenous Pathwaysupporting
confidence: 85%
“…VLP are recognized by natural antibodies and presumably trigger the classical as well as the alternative pathway of complement activation. Hence, Fc as well as complement receptors may be likely candidates for at least partial activation of DC in the absence of IFN-a/bR signaling.In support of this notion, CD86 upregulation but not CCR7 expression was impaired in IFN-a/bR À/À mice in response to RNA virus, suggesting a unique dissociation of migration and maturation events in DC responding to RNA [36].Our results are in contrast with previous observations made with model antigens, such as OVA, where a strong dependence of cross-presentation on TLR signaling was observed [22,37]. Multiple reasons may be responsible for the observed differences.…”
supporting
confidence: 61%
“…Maturation of DC is a key step for the regulation of immune responses, as resting DC appear to induce T-cell tolerance whereas only activated DC induce T-cell activation [20,21]. Furthermore, TLR signaling has been shown to promote phagocytosis by DC as well as endosomal maturation, facilitating antigen processing and presentation [22]. Most TLR share the common adaptor molecule MyD88 to activate nuclear translocation of NF-kB and the production of cytokines including .…”
mentioning
confidence: 99%
“…First, TLRs trigger the secretion of critical cytokines such as IL1, IL-6 and IL-12 by DCs, which are important for T-cell differentiation and the induction of potent adaptive immunity. Several groups have shown that conjugation of certain TLR ligands (that is, for TLR2, TLR4, TLR7 and TLR9) to peptides or proteins significantly enhances CD4 þ and CD8 þ T-cell responses compared with administration of TLR ligands or a peptide/protein mixture alone (Jackson et al, 2004;Wille-Reece et al, 2005;Blander and Medzhitov, 2006). Third, TLRs can directly stimulate the proliferation of CD4 þ and CD8 þ T cells as well as reverse the suppressive function of Treg cells (Crellin et al, 2005;Peng et al, 2005;Tabiasco et al, 2006).…”
Section: Targeting Tlrs For Cancer Therapymentioning
confidence: 99%